Physics from Symmetry - Schwichtenberg, Jakob (Springer, 2018)
In the course of studying physics I became, like any student of physics, familiar with many fundamental equations and their solutions, but I wasn’t really able to see their connection. I was thrilled when I understood that most of them have a common origin: symmetry. To me, the most beautiful thing in physics is when something incomprehensible, suddenly becomes comprehensible, because of a deep explanation. That’s why I fell in love with symmetries. For example, for quite some time I couldn’t really understand spin, which is some kind of curious internal angular momentum that almost all fundamental particles carry. Then I learned that spin is a direct consequence of a symmetry, called Lorentz symmetry, and everything started to make sense. Experiences like this were the motivation for this book and in some sense, I wrote the book I wished had existed when I started my journey in physics. Symmetries are beautiful explanations for many otherwise incomprehensible physical phenomena and this book is based on the idea that we can derive the fundamental theories of physics from symmetry.